A new species of the caridean shrimp genus Ogyrides Stebbing, 1914 (Decapoda: Ogyrididae) from the eastern tropical Pacific - Ayón-Parente, Manuel; Salgado-Barragán, José (Zootaxa, 2013)
The caridean shrimp Ogyrides wickstenae sp. nov. is described from Mazatlán, Pacific coast of Mexico. The new species is most closely related to O. tarazonai Wicksten & Méndez, 1988 and O. hayi Williams, 1981, sharing with them a single spine on the dorsal midline of the carapace. However, the new species can be distinguished from the two allied species by the presence of a single small spine on the second endopodal segment of the third maxilliped and the five-segmented car-pus of the second pereopod. A key for the Eastern Pacific species of Ogyrides is provided.